Abrocitinib for the treatment of atopic dermatitis. Issue 8 (13th September 2022) - Chaplin, Steve
Abstract : Abrocitinib (Cibinqo) is a new janus kinase inhibitor for the treatment of moderate to severe atopic dermatitis in adults and adolescents. This article reviews its properties and place in therapy.